2016
DOI: 10.5116/ijme.570d.6f2c
|View full text |Cite
|
Sign up to set email alerts
|

Cultural transition of international medical graduate residents into family practice in Canada

Abstract: ObjectivesTo identify the perceived strengths that international medical graduate (IMG) family medicine residents possess and the challenges they are perceived to encounter in integrating into Canadian family practice.MethodsThis was a qualitative, exploratory study employing focus groups and interviews with 27 participants - 10 family physicians, 13 health care professionals, and 4 family medicine residents. Focus group/interview questions addressed the strengths that IMGs possess and the challenges they face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 17 publications
1
38
0
5
Order By: Relevance
“…Power imbalance was considered a potential threat to supervisors and trainees being able to reaching agreement, with the assessment and monitoring role of the supervisor suggested to exaggerate this imbalance . Non‐hierarchical relationships were advocated to minimise this and can be fostered through trainee feedback to supervisors, and through supervisors recognising and respecting their trainees .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Power imbalance was considered a potential threat to supervisors and trainees being able to reaching agreement, with the assessment and monitoring role of the supervisor suggested to exaggerate this imbalance . Non‐hierarchical relationships were advocated to minimise this and can be fostered through trainee feedback to supervisors, and through supervisors recognising and respecting their trainees .…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that power imbalance, and its influence on agreement, may diminish with time. Between supervisors and international medical graduates (IMGs), differing expectations were suggested regarding roles, hierarchy and gender . Generally, supervisors were reported to respond to the trainee's needs, even in instances when this conflicted with their preferred supervision style .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants born in Canada were also more often correct about MAID as compared to those born elsewhere. This is not the first study that has found immigrants have greater healthcare educational needs than naturalised citizens (Triscott, Szafran, Waugh, Torti, & Barton, ). A higher level of MAID knowledge was also evident among participants who had a university degree, which again is not surprising as higher education has often been revealed as a key influence for health and healthcare knowledge.…”
Section: Discussionmentioning
confidence: 71%